Development of communication module for semi-autonomos UAV and robots - Abdul Aziz, Normaziah; Mabrouk, Ahmed Hassan (s.n, 2012)
Unmanned Aerial Vehicles (UAV) has recently attracted a lot of attention a lot of attention in the research field due to its suitable to a wide array of civil and military application. Many world class universities, as well as research centers, are currently conducting active programs concerning the different aspects of UAV.